2009
DOI: 10.1097/mbc.0b013e32832ca31f
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between chromogenic factor X and international normalized ratio differs during early warfarin initiation compared with chronic warfarin administration

Abstract: Chromogenic factor X (CFX) monitoring is necessary in patients with potential international normalized ratio (INR) artifacts during warfarin therapy. The relationship of CFX with the INR needs to be quantitated to have warfarin protocols that are equivalent with either test as a monitoring parameter. This study investigated whether the CFX/INR relationship is different during warfarin initiation compared with that during chronic warfarin therapy. Outpatients (N = 164) taking chronic doses of warfarin and inpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…The best fit model of the relationship between CFX and INR was inverse with a natural log transformation of both variables. Modeling a quadratic relationship with reciprocal transformation of INR, as has been reported in previous studies [16] showed increased sensitivity to outliers in our data. This may be because we had fewer data points at the extreme INR values and our patients were on stable warfarin dosing.…”
Section: Discussionsupporting
confidence: 67%
“…The best fit model of the relationship between CFX and INR was inverse with a natural log transformation of both variables. Modeling a quadratic relationship with reciprocal transformation of INR, as has been reported in previous studies [16] showed increased sensitivity to outliers in our data. This may be because we had fewer data points at the extreme INR values and our patients were on stable warfarin dosing.…”
Section: Discussionsupporting
confidence: 67%
“…A higher variability with recombinant thromboplastin reagents has been demonstrated in non-APS patients in the initial phase of VKA therapy as well as those with unstable INR values [23][24][25]. This has been primarily attributed to variations in the concentration of factor VII due to its short plasma half-life (t H ≈6 h).…”
Section: Inr Differences Between Different Pt Assaysmentioning
confidence: 95%
“…The supratherapeutic INR category of greater than 3.0 correlated with a mean CFX of 20.8% (range, 9% to 46%) (n=104). In 2009, Rosborough et al 27 identified that the relationship between CFX and INR varies among patients with initiation of warfarin vs those receiving long-term warfarin therapy. They reported a 7% to 18% higher level of CFX activity for a given INR value during warfarin initiation compared with patients receiving long-term warfarin therapy and suggested predictive formulas for each phase of therapy.…”
Section: Discussionmentioning
confidence: 99%